The moderating effects of Islamic religiosity in the relationship between selected Islamic microfinance products and services and entrepreneurs' business performance - Shehu, Farida Mohammed (2018)
The growing field of entrepreneurship in Nigeria has led to the development of women entrepreneurship. However, there is a rising concern about the poor business performance of women entrepreneurs because of the difficulties they face in terms of accessibility to capital and rising interest rates charged. Lack of studies on Islamic finance products as alternatives to interest-based loans and other non-financial factors affecting the business performance devoid empirical evidence to refer in overcoming the business performance issues. Hence, it is the objective of this thesis to examine the direct effects of Murabaha financing, Mudharabah savings, social capital, trade show, business advice and business monitoring on Muslim women entrepreneurs’ business performance. Drawing upon the Maqasid Al-Shari’ah philosophy, entrepreneurship and finance theories, this study embarked on a new departure from past studies by investigating the moderating role of Islamic religiosity in the research framework. A total of 519 self-modified questionnaires were distributed to Muslim women entrepreneurs in Kano State, Nigeria. Using a more current methodology of Partial Least Squares Structural Equation Modelling, the findings found Murabaha financing not significant, but Mudharabah savings, social capital, trade show, business advice and business monitoring have positive and significant influence on entrepreneurs’ business performance. Additionally, Islamic religiosity moderated (strengthened) the relationship between social capital, business advice and entrepreneurs’ business performance. This new finding on the moderating effect suggests that women entrepreneurs with higher Islamic religiosity achieve higher business performance. Overall, this study contributes to the body of knowledge in terms of integrating Islamic finance principles and ethical values in entrepreneurship. For practical contribution, this study recommends several policy reforms both at the government and practitioners’ levels in terms of application of Islamic finance products, structured, regular trainings and mobile advisory units to assist women entrepreneurs achieve higher business performance.